Long Noncoding RNA H19: A Novel Therapeutic Target Emerging in Oncology Via Regulating Oncogenic Signaling Pathways - Wu, Baokang; Zhang, Yizhou; Yu, Yang; Zhong, Chongli; Lang, Qi; Liang, Zhiyun; Lv, Chao; Xu, Feng; Tian, Yu (Frontiers in Cell and Developmental Biology, 2021)
Long noncoding RNA H19 (H19) is an imprinting gene with only maternal expression that is involved in regulating different processes in various types of cells. Previous studies have shown that abnormal H19 expression is involved in many pathological processes, such as cancer, mainly through sponging miRNAs, interacting with proteins, or regulating epigenetic modifications. Accumulating evidence has shown that several oncogenic signaling pathways lead to carcinogenesis. Recently, the regulatory relationship between H19 and oncogenic signaling pathways in various types of cancer has been of great interest to many researchers. In this review, we discussed the key roles of H19 in cancer development and progression via its regulatory function in several oncogenic signaling pathways, such as PI3K/Akt, canonical Wnt/β-catenin, canonical NF-κB, MAPK, JAK/STAT and apoptosis. These oncogenic signaling pathways regulated by H19 are involved in cell proliferation, proliferation, migration and invasion, angiogenesis, and apoptosis of various cancer cells. This review suggests that H19 may be a novel therapeutic target for cancers treatment by regulating oncogenic signaling pathways.